A case‐based analysis of the competitiveness of the North Indian sugar industry. Issue 1 (15th September 2020) - Sheetal; Singh, Randeep; Shashi; Kumar, Rajiv
Abstract : The Indian sugar industry contributes 10% to the country's agricultural GDP, and is a significant part of India's manufacturing base. Although the industry has been the focus of much attention over the years, there remains a lack of case‐based studies of its competitiveness. Using data from in‐depth interviews with executives in five North Indian sugar companies, we address this gap by applying Porter's theories on competitive advantage, in combination with a technique known as analytic hierarchical process. This allows us to measure and evaluate the industry's competitiveness, and provides a detailed view of the factors that influence it. While this study focuses on the North Indian sugar industry, the techniques used could easily be adapted to the assessment of competitiveness in other sectors to guide practitioners' efforts to improve the competitive performance of their company.